Protective role of commensal bacteria in Sjögren Syndrome. (September 2018) - Zaheer, Mahira; Wang, Changjun; Bian, Fang; Yu, Zhiyuan; Hernandez, Humberto; de Souza, Rodrigo G.; Simmons, Ken T.; Schady, Deborah; Swennes, Alton G.; Pflugfelder, Stephen C.; Britton, Robert A.; de Paiva, Cintia S.
Abstract: CD25 knock-out (CD25KO) mice spontaneously develop Sjögren Syndrome (SS)-like inflammation. We investigated the role of commensal bacteria by comparing CD25KO mice housed in conventional or germ-free conditions. Germ-free CD25KO mice have greater corneal barrier dysfunction, lower goblet cell density, increased total lymphocytic infiltration score, increased expression of IFN-γ, IL-12 and higher a frequency of CD4 + IFN-γ + cells than conventional mice. CD4 + T cells isolated from female germ-free CD25KO mice adoptively transferred to naive immunodeficient RAG1KO recipients caused more severe Sjögren-like disease than CD4 + T cells transferred from conventional CD25KO mice. Fecal transplant in germ-free CD25KO mice reversed the spontaneous dry eye phenotype and decreased the generation of pathogenic CD4 + IFN-γ + cells. Our studies indicate that lack of commensal bacteria accelerates the onset and severity of dacryoadenitis and generates autoreactive CD4 + T cells with greater pathogenicity in the CD25KO model, suggesting that the commensal bacteria or their metabolites products have immunoregulatory properties that protect exocrine glands in the CD25KO SS model. Highlights: Germ-free (GF) environment worsens severity and accelerates the onset of autoimmunity in the CD25KO Sjögren Syndrome Model. GF CD25KO mice have greater dry eye phenotype and greater frequency of CD4 + IFN-γ + cells than conventional CD25KO mice. Adoptive transfer of GF CD25KO CD4+ T cells causes more severe disease in Rag1KO recipients than conventional CD25KO T cells. Fecal transplant in GF CD25KO mice ameliorates autoimmunity by decreasing generation of pathogenic CD4 + IFN-γ + cells. Neutralization of IL-12 in GF CD25KO mice decreases the severity of dacryoadenitis.